2014
DOI: 10.1097/ta.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preinjury anticoagulants and prescription antiplatelet agents on outcomes in older patients with traumatic brain injury

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 13 publications
1
66
1
2
Order By: Relevance
“…It has been suggested that an increase of 1% -2% of ICH rates can negate the benefits of antithrombotic therapy [11]. It should be noted that while the mortality of our study is disproportionately higher to what has been described in the literature [29] [30], this is the first paper, to our knowledge, that assesses the adverse effects of APAC use on patients presenting with surgically-treated intracranial hemorrhage.…”
Section: Discussioncontrasting
confidence: 37%
See 3 more Smart Citations
“…It has been suggested that an increase of 1% -2% of ICH rates can negate the benefits of antithrombotic therapy [11]. It should be noted that while the mortality of our study is disproportionately higher to what has been described in the literature [29] [30], this is the first paper, to our knowledge, that assesses the adverse effects of APAC use on patients presenting with surgically-treated intracranial hemorrhage.…”
Section: Discussioncontrasting
confidence: 37%
“…However, the premorbid use of APACs has proven to be a difficult challenge in the presence of a neurosurgical emergency. They pose a risk factor for intracranial hemorrhage [1] and have been associated with poor prognoses in the settings of both spontaneous as well as trauma-related hemorrhage [6]- [10]. With respect to spontaneous hemorrhage, antithrombotic therapy is associated with 7000 of the 60,000 (12%) intracerebral hemorrhages (ICH) that occur annually in the United States (which represents approximately 1% of incidental strokes) [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In clinical TBI, intracerebral vessel occlusion with subsequent ischemia worsens the outcome 8, 9, 11, 12. However, the potential use of conventional anticoagulants in patients with TBI is met with controversy, due to the increased risk of intracerebral hemorrhage 13, 14, 15, 16, 17, 18. Previous studies from our laboratory have shown that both genetic deficiency and pharmacological inhibition of the coagulation factor XII (FXII), a protease that initiates the activation of the intrinsic coagulation cascade, protect mice from ischemic stroke without increasing bleeding tendencies 19, 20.…”
mentioning
confidence: 99%